Pelatihan dan Pendampingan Pembuatan Es Krim Ubi Ungu untuk ibu PKK di Desa Lelong, Lombok Tengah - Fahrullah Fahrullah; Azhary Noersidiq; Eka Nurminda Dewi Mandalika; Rabyatul Auliah; Miftahul Jannah; Sukirno Sukirno (Jurnal Pengabdian Masyarakat Sains Indonesia, 2026)
Processing animal-based food products is an activity that transforms raw materials into products desired by consumers. In addition, food processing can produce products with desirable characteristics, such as safety, nutritional value, and sensory acceptability. One example of an animal-based food product is ice cream, which is primarily made from milk. The purpose of this community service activity was to provide the residents of Lelong Village with an understanding of food diversification through training on ice cream production utilizing a local food resource, namely purple sweet potato. The methods employed in this activity included lectures, discussions, demonstrations of ice cream production, mentoring, and final evaluation. The results of the community service activity showed that 25% of participants considered the program beneficial, while 75% considered it highly beneficial. Furthermore, 100% of participants stated that the activity was highly relevant to the needs of the Lelong Village community, increased their motivation after participating in the purple sweet potato ice cream processing training, and encouraged community self-reliance. The results also indicated that participants were highly enthusiastic in receiving the materials, motivated in producing ice cream products, and had gained the knowledge and skills necessary to process ice cream with the addition of purple sweet potato.